How Does China Economic Policy Uncertainty (Epu) Impact Copper-Firms Stock Returns and Copper Prices Returns? - Espinosa-Mendez, C (Emerald Publishing, 2023)
Purpose: This study focuses on how China EPU may impact copper-firms stock returns and also how China EPU mediates between stock returns and copper prices returns. Design/methodology/approach: The sample consists of 44 copper firms from January 2011 to March 2022. The study also considers a subsample of 29 net-exporters countries. Panel data methodology is used, allowing to control for unobservable heterogeneity and endogeneity problems. The equations are estimated through a dynamic panel using the generalized methods of moments (GMM). Findings: China EPU has a negative and statistically significant relationship with stock returns. Copper price returns are positively associated with stock returns. This research also considers two scenarios: high and low levels of China EPU. For high levels of China EPU states it is reported a negative relationship between stock returns and China EPU and copper price returns show a positive relationship with stock returns. Research limitations/implications: There is need to explore other metals for what China exhibits a high demand and observe if China EPU and Global EPU have similar impacts on stock returns. It will be useful to identify main firm s consumers of copper and these other metals to explore the relationship between EPU and stock returns. Originality/value: To the best of the authors’ knowledge, this is the first paper that analyzes China EPU index and its impact on both copper-firms stocks returns and on changes in copper prices. This is done using all public copper firms worldwide. © 2023, Emerald Publishing Limited.